Technological Innovations in Raptor Conservation: A Systematic Review of Methods and Applications - Espinosa , Gonzalo; Guerra , Julio; Naranjo , Francisco; Mosquera , Luis (Data and Metadata, 2025)
Introduction: Raptors play a critical role in ecosystem stability, yet many species face significant population declines due to habitat loss, climate change, and human-induced mortality. Technological advancements such as satellite telemetry, machine learning, bioacoustics, and radar tracking have transformed raptor research, enabling precise monitoring and data-driven conservation strategies. Methods: A systematic review using the PRISMA methodology was conducted on the most relevant methodologies and technologies used in raptor research. Data from multiple studies employing satellite telemetry, habitat modeling, genetic analysis, bioacoustics, and conservation management tools were synthesized to evaluate their effectiveness. Results: Findings indicated that satellite telemetry remains the most widely used tool for tracking raptor movements, while machine learning and bioacoustics are emerging as powerful methods for habitat assessment. Population viability models frequently overlook key demographic factors, such as the age of first breeding, which can significantly impact conservation outcomes. Conclusions: Integrating advanced technologies with standardized methodologies is essential for improving raptor conservation. Future research should focus on refining predictive models, enhancing data-sharing platforms, and ensuring technological advancements translate into effective conservation policies.